Investing in Human Capital Management for Firm Performance: Liability or Strategic Alignment? - Gautam, Prakash Kumar; Gautam, Rishi Raj (Management Dynamics, 2022)
A firm’s sustainable performance is a burgeoning issue globally. It is the strategic choice of the firm whether it should invest in its human resources. This study examines the role of human capital management in determining firm performance. HR competencies, HR practices, HR systems, and HR deliverables were selected as the dimensions of human capital management. Employee satisfaction was the mediating variable. Data were collected from a survey of conveniently selected 305 employees of purposively selected life insurance companies in Nepal. The results of the study revealed a positive significant impact of each component of human capital management and overall human capital management on firm performance, concluding that investment in human capital management is the strategic alignment rather than the liability. Firms investing more in human capital enhance their financial performance for sustainable growth. This study contributes to elaborating the resource-based view for creating dynamic capability of resources from effective development and mobilization of human resources.